DEVELOPMENT OF ANDROID-BASED INTERACTIVE MULTIMEDIA ON THE CONCEPT OF CHANGES IN THE FORM OF OBJECTS IN GRADE V ELEMENTARY SCHOOL - Ririn Handayani; Encep Andriana; Aan Subhan Pamungkas (Universitas Majalengka, 2023)
This research aims to develop Android-based interactive multimedia to take advantage of currently developing information and communication technologies and learning media innovations in elementary schools. The research method used in learning media development adopts the development design according to Borg and Gall, which has been modified by Sugiyono and has six stages: analyzing the problem, designing the product, validating the product design, revising the product design, and testing the product. The data collection technique used in this study was a questionnaire or questionnaire that was used to determine the feasibility of the product and to know the student’s responses to the product being developed. The data analysis technique changes the qualitative assessment into a quantitative one according to the scoring rules. The results of this study are in the form of Android-based interactive multimedia on the concept of changing the shape of objects with a feasibility assessment of a team of material experts of 89% and a group of media experts of 91%, so an average feasibility assessment of 90% is obtained with the “very feasible” category. The results of student responses received an average of 93% in the “excellent” category. Based on the results of this study, it can be concluded that interactive multimedia based on Android on the concept of changing the shape of objects developed in class V students is “very feasible” to be used in learning with material changes in the form of things. Tujuan penelitian ini yaitu untuk mengembangkan multimedia interaktif berbasis Android guna memanfaatkan teknologi informasi dan komunikasi yang berkembang saat ini dan juga sebagai inovasi media pembelajaran di sekolah dasar. Metode penelitian yang digunakan dalam pengembangan media pembelajaran ini mengadopsi dari desain pengembangan menurut Borg dan Gall yang telah dimodifikasi oleh Sugiyono yang memiliki enam tahapan yaitu menganalisis masalah, mendesain produk, memvalidasi desain produk, merevisi desain produk, dan menguji coba produk. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah angket atau kuesioner yang digunakan untuk mengetahui penilaian kelayakan produk dan mengetahui respon peserta didik terhadap produk yang dikembangkan. Teknik analisis data yang digunakan ialah dengan mengubah penilaian kualitatif menjadi kuantitatif sesuai dengan aturan pemberian skor. Hasil penelitian ini berupa multimedia interaktif berbasis Android pada konsep perubahan wujud benda dengan penilaian kelayakan tim ahli materi sebesar 89% dan tim ahli media sebesar 91%, maka didapatkan rata-rata penilaian kelayakan sebesar 90% dengan kategori “sangat layak”. Hasil respon peserta didik memperoleh rata-rata sebesar 93% dengan kategori “sangat baik”. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa multimedia interaktif berbasis Android pada konsep perubahan wujud benda yang dikembangkan pada peserta didik kelas V “sangat layak” untuk digunakan dalam pembelajaran dengan muatan materi perubahan wujud benda.